The Persean Ethic: Consistency of Belief and Action in Managerial Practice - Joseph A. Raelin (Human Relations, 1993)
The Persean ethic in managerial practice refers to the willingness of managers to follow through on their espoused beliefs with others in their immediate working network. It is considered to be among the most important of managerial practices since through it managers can monitor their beliefs to ensure that their actions are consistent with otherwise salutary espoused theories. In order to assess the dependent variable of Persean conduct, or consistency of belief and action, the core respondents' immediate work set, including their superior, peers, and subordinates, were surveyed as well as themselves. In an attempt to create an explanatory model of Persean conduct, individual personality and background factors, situational characteristics, their interaction, and learning factors were evaluated. Respondents were found to vary on Persean conduct, the Persean ethic was found not to be unidimensional, and although each of the independent variable clusters was represented in the predictor list, personality factors dominated as explanatory variables.
Keywords: M51; M10; M12; J28; O15; 650; Humanism; Democratic organization; Consistency of belief and action; Perception; Attribution; Feedback